Pengaruh Pemberian Beberapa Jenis Pupuk Organik Terhadap Penyakit Karat Kedelai dan Produksinya - Eko Agus Martanto; Adelin Tanati; Samen Baan; Claudia N Risamasu (AGRICOLA, 2021)
This study aims to determine the effect of giving several organic fertilizer formulations to the intensity of soybean leaf rust disease and its production, which in turn can increase farmers' income in this area. The study was conducted using randomized block design (RBD) with 3 replications. The treatments were husk ash, compost, chicken manure, and goat manure. The parameters observed included leaf rust disease intensity, disease progression rate, plant height, number of leaves, number of branches, weight of 100 seeds and weight of seeds per plot. Data analysis was performed using Analysis of Variance (ANOVA), if the treatment has a significant effect, it is followed by the DMRT test at the 95% level. The result showed that (1) the fertilizer formulation given caused different responses to the parameters of soybean rust disease intensity, plant height, number of leaves, number of branches, weight per 100 seeds and weight of seeds per plot, (2) The best fertilizer for controlling soybean leaf rust disease is goat manure, and (3) the best fertilizer formulation to produce production is abusekam with a production of 2156.66 gr / plot (equivalent to 3.594 tons / ha)